1989
DOI: 10.1210/jcem-68-1-223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogens and Calcium on Calcitonin Secretion in Postmenopausal Women*

Abstract: The protective action of estrogens on bone mass may be mediated by an increase in calcitonin (CT) secretion. We reevaluated this hypothesis using a method for measuring CT in extracts of serum that allows sensitive specific measurement of CT monomer. We studied seven healthy postmenopausal women before and on the 7th and 28th days of each of three 4-week treatment periods: estrogen (estradiol valerate; 2 mg/day), calcium supplement (1500 mg/day), and estrogen plus calcium; the three cycles were separated by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
4
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…The lack of a stimulatory effect of estrogen therapy on baseline calcitonin levels in this study of healthy postmenopausal women supports some (15)(16)(17)(18) but not all (1,13,14) previous reports. In one study an increase in basal calcitonin levels occurred only after 6 months of therapy (23) suggesting that es¬ trogen may only have long-term effects on calcito¬ nin secretion.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The lack of a stimulatory effect of estrogen therapy on baseline calcitonin levels in this study of healthy postmenopausal women supports some (15)(16)(17)(18) but not all (1,13,14) previous reports. In one study an increase in basal calcitonin levels occurred only after 6 months of therapy (23) suggesting that es¬ trogen may only have long-term effects on calcito¬ nin secretion.…”
Section: Discussionsupporting
confidence: 89%
“…There have been reports of lower cal¬ citonin levels in osteoporotic women compared to normal postmenopausal women suggesting a role for calcitonin deficiency in the pathogenesis of osteoporosis (8,9), but this remains controversial with other studies showing no difference (10) or higher calcitonin levels in osteoporosis (11,12).The effect of oral estrogen replacement on cal¬ citonin secretion is controversial with three similar studies from the same group showing a rise in cal¬ citonin levels (1,13,14) despite a fall in plasma cal¬ cium while other studies show lower or unchanged calcitonin levels after estrogen therapy (15)(16)(17)(18). Following baseline measurement of calcitonin and ionized calcium in the fasting state, the effect of calcium infusion on calcitonin levels was studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We indeed demonstrated that es trogen replacement therapy in healthy postmenopausal women did not stimulate CT secretion, as claimed by oth ers [3], but, on the contrary, induced a slight reduction in basal CT levels, consistent with the well-known inhibitory effects of estrogens on bone turnover [16]. Another study in male renal stone formers also supports our hypothesis.…”
Section: Osteoporosis and Estrogen Replacement Therapy: Effects On Ctsupporting
confidence: 88%
“…Estrogens can act on both synthesis and release of CT. Contrary to these findings, Body et al (1989) concluded that estrogen did not stimulate secretion of CT in postmenopausal women. Eriksen et al (1988) suggested that estrogen has a direct effect on bone cells, as mRNA for estrogen receptor protein was localized within the cytoplasm of normal human osteoblasts.…”
Section: Discussionmentioning
confidence: 61%